MATHEMATICAL LITERACY SKILLS OF JUNIOR HIGH SCHOOL STUDENTS OF 21 CENTRAL BENGKULU IN THE INDEPENDENT CURRICULUM - Izzah Afriyanti; Mardiah Syofiana; Masri (EMTEKA: Jurnal Pendidikan Matematika, 2025)
Mathematical literacy focuses on students' ability to analyze, solve, and interpret mathematical problems in a variety of contexts. These abilities need to be measured so that they can be a reference to find ways to improve students' mathematical literacy skills. The shift to an independent curriculum can be a new gateway for learning in Indonesia to improve students' mathematical skills. The purpose of this study is to determine the mathematical literacy ability of grade VII students of SMP Negeri 21 Bengkulu Tengah in implementing the independent curriculum. This study investigated 25 students who used the independent curriculum. As a method of data collection, written tests, interviews, and documentation were used. The results of the study show that most students are still at a low level of mathematical literacy. 8 students reached level 1c, 2 students were at level 1b, and only 1 student reached level 1a. On the PISA scale, level 1c is the lowest level, where students can only answer questions with very explicit information, while level 3 shows the ability to use reasoning and apply mathematical concepts in more complex contexts. This low achievement is influenced by the lack of habit of solving contextual problems, difficulty understanding the information in the problem, and limited ability in basic calculation operations. These findings show the need for improvement in the approach to mathematics learning with an emphasis on contextual problems, and the practice of applied numeracy skills. Literasi matematis berfokus pada kemampuan siswa untuk menganalisis, memecahkan, dan menafsirkan masalah matematis dalam berbagai konteks. Kemampuan tersebut perlu diukur sehingga dapat menjadi acuan untuk mencari cara bagaimana meningkatkan kemampuan literasi matematis siswa. Pergeseran ke kurikulum merdeka dapat menjadi gerbang baru bagi pembelajaran di Indonesia untuk meningkatkan kemampuan matematis siswa. Tujuan penelitian ini adalah untuk mengetahui kemampuan literasi matematis siswa kelas VII SMP Negeri 21 Bengkulu Tengah dalam menerapkan kurikulum merdeka. Penelitian ini menyelidiki 25 siswa yang menggunakan kurikulum merdeka. Sebagai metode pengumpulan data digunakan tes tertulis, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa sebagian besar siswa masih berada pada level literasi matematis rendah. 8 siswa mencapai level 1c, 2 siswa berada di level 1b, dan hanya 1 siswa mencapai level 1a. Dalam skala PISA, level 1c merupakan tingkat terendah, di mana siswa hanya dapat menjawab soal dengan informasi yang sangat eksplisit, sedangkan level 3 menunjukkan kemampuan menggunakan penalaran dan menerapkan konsep matematika dalam konteks yang lebih kompleks. Rendahnya capaian ini dipengaruhi oleh kurangnya kebiasaan menyelesaikan soal kontekstual, kesulitan memahami informasi dalam soal, serta terbatasnya kemampuan dalam operasi hitung dasar. Temuan ini menunjukkan perlunya perbaikan dalam pendekatan pembelajaran matematika dengan menekankan pada soal-soal kontekstual, dan latihan keterampilan berhitung yang aplikatif.